Implementasi Pelatihan Desain Grafis di Balai Pelatihan Kerja Desa Kronggen dalam Memperoleh Kesempatan Kerja - Shabrina Khilda Zulfia; Rona Fristi Febbilla; Wasis Wijayanto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The problem that the Indonesian people are still facing is the employment problem. The high workforce every year is not equipped with appropriate skills and expertise. It is hoped that this training program can create a workforce that has skills and expertise in their field. Qualitative research method with a descriptive approach. Data collection techniques are through observation, interviews and literature study. The aim of this research is to provide participants with graphic design knowledge and skills, so that participants can apply the skills they have acquired in opening their own business. The results of this research are that the Kronggen village BLK annually carries out graphic design training. In 2024, for the first time, the Kronggen village BLK will carry out cosmetology training.